2016
DOI: 10.1038/srep33676
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Silencing of Histone Deacetylase 9 Expression in Podocytes Attenuates Kidney Injury in Diabetic Nephropathy

Abstract: Podocyte dysfunction is important in the onset and development of diabetic nephropathy (DN). Histone deacetylases (HDACs) have been recently proved to play critical roles in the pathogenesis of DN. As one subtype of the class IIa HDACs, HDAC9 is capable to repress/de-repress their target genes in tumor, inflammation, atherosclerosis and metabolic diseases. In the present study, we investigate whether HDAC9 is involved in the pathophysiologic process of DN, especially the podocyte injury. Firstly, we explored t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 45 publications
1
43
1
Order By: Relevance
“…Accumulating evidence indicates that DN is more like a “podocyte disease” [9-11]. Some clinical studies [12, 13] showed that the number of podocytes was reduced by detachment, or apoptosis as the primary reason. As podocytes are terminally differentiated epithelial cells and located in the glomerular basement membrane, their apoptosis is associated with their inability to be replaced or regenerated, ultimately resulting in glomerulosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence indicates that DN is more like a “podocyte disease” [9-11]. Some clinical studies [12, 13] showed that the number of podocytes was reduced by detachment, or apoptosis as the primary reason. As podocytes are terminally differentiated epithelial cells and located in the glomerular basement membrane, their apoptosis is associated with their inability to be replaced or regenerated, ultimately resulting in glomerulosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, HDAC4 contributes to podocyte injury and is one of the dire components of a signal transduction pathway that links renal injury to autophagy in diabetic nephropathy. [11] HDAC9 [43] HDAC9 and found that HDAC9 expression was significantly up-regulated in high glucose (HG)-treated mouse podocytes, as well as kidney tissues from diabetic db/db mice and patients with DN [43] In diabetic db/db mice, silencing of HDAC9 diminished the glomerulosclerosis, inflammatory cytokine release, podocyte apoptosis and renal injury. Together, these data indicate that HDAC9 may be tangled in the process of DN, especially podocyte injury.…”
Section: Hdac 4 Plays Important Role In Dn [11]mentioning
confidence: 99%
“…[2] 2. Many isoform of HDAC are up-regulated in diabetic Nephropathy, many study suggest HDAC 2/4/ 9 [10,11,43] plays important role in development of diabetic nephropathy which makes more difficult in interpretation and coming to conclusion which isoform should be targeted in vivo study.…”
Section: Figure From Sourcementioning
confidence: 99%
“…[14] HDAC9 [15] HDAC9 and found that HDAC9 expression was significantly up-regulated in high glucose (HG)-treated mouse podocytes, as well as renal tissues from diabetic db/db mice and patients with DN. [15] In diabetic db/db mice, silencing of HDAC9 diminished the glomerulosclerosis, inflammatory cytokine release, podocyte apoptosis and kidney injury. Collectively, these data indicate that HDAC9 may be tangled in the process of DN, especially podocyte injury.…”
Section: Hdac 4 Plays Important Role In Dn [14]mentioning
confidence: 99%
“…[15] ANIMAL STUDY [16] In vivo and in vitro under the diabetic state, the expression of DNA methyltransferase 1 (Dnmt1), nuclear factor Sp1, and nuclear factor kappa B (NFκB)-p65 evidently augmented in podocytes. The amplified expression of Dnmt1 was decreased after treatment with 5-azacytidine or 5-aza-2'-deoxycytidine or knockdown of Dnmt1 restored decreased podocyte slit diaphragm proteins following from hypermethylation and enhanced podocyte motility.…”
Section: Hdac 4 Plays Important Role In Dn [14]mentioning
confidence: 99%